Carcinoid tumor associated with adjacent dysplastic columnar epithelium in the renal pelvis: A case report and literature review. Issue 1 (8th December 2015) - Kim, Sung Sun; Choi, Chan; Kang, Taek Won; Choi, Yoo Duk
Abstract : Carcinoid tumors are well documented in the pulmonary and gastrointestinal systems, but very rare in the urinary tract, especially in the renal pelvis. We report on a 60‐year‐old female patient who presented with left flank pain and fever. Abdominal computed tomography demonstrated a heterogeneously enhancing mass in the left renal pelvis and a stone at the left proximal ureter. Multiple parenchymal lesions were also observed, which were identified as uneven caliectasis displaying air‐fluid levels and renal parenchymal atrophy. The patient underwent simple nephro‐ureterectomy. Macroscopically, a polypoid mass was observed in the renal pelvis. Microscopically, the tumor revealed acinar, tubular, and solid pattern and was composed of small, monotonous and hyperchromatic cells. Lining epithelia in renal pelvis and ureter revealed columnar epithelia with dysplastic change. The tumor cells were positive for chromogranin A, synaptophysin, CD56, and focally positive for cytokeratin. Immunohistochemical staining of synaptophysin and chromogranin A highlighted the neuroendocrine cells in the columnar epithelium. Ki‐67 (1:50; MIB‐1) labeling index was less than 1% in the area with highest uptake. We report here a case of carcinoid tumor of the renal pelvis that was associated with adjacent dysplastic columnar epithelium.